Bio-charge Elastic Characterization for A Qualitative Perspective of Innovative Bio-Composite Materials - M. Jammoukh; K. Mansouri; B. Salhi; E. Abtal (Iraqi Journal of Science, 2021)
In order to save natural resources, recycling necessarily becomes a top priority for all of us, to save exhaustible resources, produce green energy and preserve the environment.In this perspective, we are trying to valorize a waste of animal origin, largely neglected by the actors of materials, through an industrial transformation into a biological charge to make new sustainable bio-composite materials.Using a tensile test bench, we try to mechanically characterize this biomaterial of renewable resources that, unlike eco-composites, has been neglected by the material actors.Obtained from waste, with a high recycling potential and from renewable resources, the bio-charge to be analyzed will be injected, later in different polymer materials in order to support the evolution of their physicochemical properties: resistance to elongation, wear, heat, corrosion, etc.Consequently, we will be able to contribute to an eco-design of sustainable materials with safeguarding exhaustible resources and preserving our environment